PF.26 Prenatal Detection of Structural Cardiac Defects and Presence of Associated Anomalies: A Prospective Study of 1, 244 Fetal Echocardiograms. (26th April 2013) - Farrell, S; McTiernan, A; Walsh, CA; Mulcahy, C; McMahon, C; McAuliffe, FM
Abstract : Background: Our unit offers a comprehensive fetal echocardiograhy service to expectant mothers who are at increased risk of having a fetus with a cardiac defect. Methods: A prospective study from January 2007 to December 2011. Cases of fetal echocardiography were extracted and analysed for referral indication, the presence of extra-cardiac anomalies on ultrasound and, where applicable, the results of invasive testing for fetal karyotype. Indications for fetal echocardiography were classified as abnormal anatomy scan, family history, previously affected child, maternal medical disease (diabetes, epilepsy etc) or other (including IUGR and teratogen exposure). Results: During the 5-year study period 1, 244 echocardiograms were performed in our unit, with 242 (19.5%) cardiac defects detected. The most common defects were AVSD (n = 36), VSD (n = 26), transposition (n = 15), tetralogy of Fallot (n = 15), HLHS (n = 27), coarctation (n = 6) and valvular cardiac defects (n = 30). Abnormal mid-trimester fetal anatomy scan was the best indicator for detecting cardiac defects on echocardiography, compared to all other indications (p < 0.0001). Invasive testing for karyotype was performed for 44% of cases, of which 51% were abnormal. 37% (n = 89) of those with a cardiac anomaly also had an extra-cardiac defect. The presence of extra-cardiac defects was associated with a significantly higher rate of abnormal fetal karyotype (p < 0.0001). Conclusion: Most congenital cardiac defects occur in a low risk population, highlighting the importance of the 20-week anomaly scan for detection of cardiac and other defects prenatally. Significant numbers of chromosomal and extra-cardiac defects in this study emphasise the importance of thorough evaluation of any fetus identified with a cardiac defect.